Dissenting migrants: the undocumented youth struggle over rights and belonging in the United States - Cardoso, Andréia Fressatti (2025)
The aim of this dissertation is to assess the experiments on rights and belonging of the undocumented youth movement in the American public scene. We began questioning if the subject of rights must necessarily be a (national) citizen, framing the issue of the right to have rights and its companion, the right to belong, through the lenses of undocumented migrants. By critically engaging with Arendt\'s perplexities of the rights of man and Rancière\'s politics of human rights, we assess the claim for rights of the undocumented youth in the United States, also known in literature as the 1.5 generation. Since they grew up interacting with state institutions that do not demand papers, such as school, they developed their legal consciousness based on stigma rather than fear, and feel that their belonging to the community had been robbed once they transitioned to adulthood. We follow how the youth were mobilized first around the \"Dreamer\" identity and reclaimed it through more intersectional lenses, proposing two claims in the American public scene: \"undocumented and unafraid\" and \"home is here.\" Whereas the former is interpreted as an assertion of rights subjectivity despite and through their deportable bodies\' vulnerability, the latter is read as a claim for belonging and citizenship in a country that does not recognize such a claim. As we recount the undocumented struggle around the Development, Relief, and Education for Alien Minors Act (DREAM Act) and the Deferred Action for Childhood Arrivals (DACA), we propose the framework of citizenship as belonging to analyze the different experiments in rights and belonging that were advanced by these undocumented migrants. We argue that membership and belonging refer to different definitions of citizenship. Membership, which is directly challenged by the claim of undocumented migrants to a \"home,\" is an exclusive, bounded, and bordered category, with close ties to the nation-state and its emplacement tool, nationality. Belonging, on the other hand, is evaluated in three interconnected dimensions: (i) the dialogical construction of the self; (ii) the performative claim of the right to have rights; and (iii) the aesthetic claim of the right to belong. Therefore, by defining themselves as \"undocumented and unafraid,\" and claiming the U.S. as their home, including by enacting law and legal language, the undocumented youth positioned their right to belong and enacted their meanings of citizenship, which are not necessarily linked to papers. This research is positioned in the fields of critical citizenship and migration studies, and follows a grounded theoretical approach. Methodologically, migrant narratives, collected through in depth interviews conducted in the United States between 2021 and 2024, have been centered and presented horizontally to the literature\'s concepts and understandings of the struggle